Dehorned reindeer, Woodland Park, 1898 - Wilse, Anders Beer, 1865-1949 (1898)
Kjellman supervised the Teller Reindeer Station at Port Clarence, Alaska. In 1898 he accompanied the Lapland-Yukon Relief Expedition to Seattle and was photographed here in Woodland Park. Stamped on verso: Scenic Fotografer, McDonald Blk. 811-2nd Ave. Seattle, Wash. Caption on image: A dehorned Reindeer. Wilse & Kirk Photo. Wilse 559 PH Coll 285.33 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number